Chromosome localization of the ribosomal genes 18S and 5S in four stocks of rainbow trout (Oncorhynchus mykiss) from cultivated and naturalized stocks in Brazil - Porto-Foresti, Fábio (2004)
In the present study, fluorescence in situ hybridization (FISH) was employed to determine the chromosomal location of genes 18S rDNA and 5S rDNA in four rainbow trout stocks. In specimens from the stocks of Núcleo Experimental de Salmonicultura de Campos do Jordão and Gavião river, 18S genes were located at a subterminal position in the long arms of two submetacentric chromosomes, whereas in specimens from stocks of Mount Shasta and Teresópolis they were found in the short arms. In all analyzed stocks, 5S genes were located in two chromosome pairs. In a subtelocentric pair, 5S genes were present in the short arms and, in the other submetacentric pair, 5S genes were at an interstitial position. In the latter, 18S and 5S genes were contiguous. Taking into account that both 18S and 5S rDNA genes have been localized in the short arm of a submetacentric chromosome in almost all rainbow trout samples so far studied, the presence of such genes in the long arm, as seen in the samples from Núcleo Experimental de Salmonicultura de Campos do Jordão and Gavião river, supports the hypothesis of a pericentric inversion involving this chromosome segment in the ancestor line of these stocks. The observed polymorphism allowed the identification of a very useful genomic marker, and may therefore constitute an important tool in the genetic management of rainbow trout stocks.